Global burden of nasopharyngeal carcinoma attributable to alcohol use: a 1990–2021 analysis with projections to 2040 - Lu, Zhenyi; Yang, Shujun; Dai, Mengqi; Wu, Guixiang; Wang, Fabao; Zhang, Kai (Frontiers in Public Health, 2025)
BackgroundNasopharyngeal carcinoma attributable to alcohol use (NPC-AU) contributes substantially to global cancer mortality and disability, yet its temporal and geographic patterns remain incompletely described.ObjectivesTo assess the global, regional, and national burden of NPC-AU from 1990 to 2021 and project trends through 2040.Material and methodsUsing GBD 2021 data, global, regional, and national age-standardized mortality rates (ASMR) and disability-adjusted life-years rates (ASDR) attributable to alcohol were evaluated. Trends were quantified by average annual percentage change (AAPC) and projections were generated using Bayesian age–period–cohort models.ResultsFrom 1990 to 2021, global ASMR declined from 0.31 to 0.19 per 100,000 population (AAPC −1.66; 95% CI −1.79 to −1.52) and ASDR fell with an AAPC of −1.72 (95% CI −1.87 to −1.57). Male ASMR decreased from 0.42 to 0.27 per 100,000 (AAPC −1.60), and female ASMR from 0.21 to 0.12 per 100,000 (AAPC −2.25). High-middle SDI regions saw ASMR drop from 0.50 to 0.28 per 100,000 (AAPC −1.97), whereas low-middle SDI regions experienced an increase from 0.09 to 0.11 per 100,000 (AAPC 0.72). Regionally, East Asia's ASMR declined at an AAPC of −2.70, Southern Latin America at −3.13, and Southeast Asia increased at 1.76. Age-specific peaks in ASMR shifted from 55–59 and 65–69 years in 1990 to 65–69 and 70–74 years in 2021. Projections forecast male ASMR of 0.35 per 100,000 (95% UI 0.03–0.67) and female ASMR of 0.02 per 100,000 (95% UI 0.00–0.04) by 2040.Conclusions and significanceAlthough global ASMR and ASDR for NPC-AU declined markedly from 1990 to 2021, rising burdens in lower-SDI regions, persistent male predominance, and shifting peaks to older age groups highlight the need for targeted alcohol-control policies and age-tailored screening.